Experimental and numerical assessment of grain boundary energies in polycrystalline uranium dioxide. Issue 12 (September 2020) - Ksibi, A.; Bourasseau, E.; Iltis, X.; Drouan, D.; Gaudet, M.; Germain, A.; Pena, A.; Lapertot, G.; Brison, J.-P.; Belin, R.C.
Abstract: Uranium dioxide ceramics are widely used as nuclear fuels. Thus, it is important to understand the role of the grain boundaries (GBs) which decisively govern the properties of these polycrystalline materials and subsequently determine their performances. Here, we report a coupled numerical - experimental approach enabling to assess GB energies. Firstly, GB formation energies (γgb ) were computed for 34 symmetric tilt GBs in UO2 with molecular dynamics simulations at 1700 K. The surface energies (γS ) relative to the respective planes of these GBs were calculated as well. The Herring relation was then used to assess the dihedral angles Ψ of the corresponding GB grooves. Secondly, a UO2 ceramic sample was annealed at 1673 K to obtain GB grooves. The CSL GBs of interest were identified by EBSD and their Ψ angles determined by AFM. Computed and measured Ψ values were found to be very close.